Barriers and enablers to the implementation of protocol-based imaging in pancreatic cancer: A qualitative study using the theoretical domains framework - Maharaj, Ashika D. (PLoS One, 2020)
BACKGROUND: Accurate pre-operative imaging plays a vital role in patient selection for surgery and in allocating stage-appropriate therapies to patients diagnosed with pancreatic cancer (PC). This study aims to: (1) understand the current diagnosis and staging practices for PC; and (2) explore the factors (barriers and enablers) that influence the use of a pancreatic protocol computed tomography (PPCT) or magnetic resonance imaging (MRI) to confirm diagnosis and/or accurately stage PC. METHODS: Semi-structured interviews were conducted with radiologists, surgeons, gastroenterologists, medical and radiation oncologists from the states of New South Wales (NSW) and Victoria, Australia. Interviews were conducted either in person or via video conferencing. All interviews were recorded, transcribed verbatim, de-identified and data were thematically coded according to the 12 domains explored within the Theoretical Domains Framework (TDF). Common belief statements were generated to compare the variation between participant responses. FINDINGS: In total, 21 clinicians (5 radiologists, 10 surgeons, 2 gastroenterologists, 4 medical and radiation oncologists) were interviewed over a four-month-period. Belief statements relevant to the TDF domains were generated. Across the 11 relevant domains, 20 themes and 30 specific beliefs were identified. All TDF domains, with the exception of social influences were identified by participants as relevant to protocol-based imaging using either a PPCT or MRI, with the domains of knowledge, skills and environmental context and resources being offered by most participants as being relevant in influencing their decisions. CONCLUSIONS: To maximise outcomes and personalise therapy it is imperative that diagnosis and staging investigations using the most appropriate imaging modalities are conducted in a timely, efficient and effective manner. The results provide an understanding of specialists’ opinion and behaviour in relation to a PPCT or MRI and should be used to inform the design of future interventions to improve compliance with this practice.